2021
DOI: 10.1029/2021gl093155
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Height Anomalies of the Arctic Ocean From ICESat‐2: A First Examination and Comparisons With CryoSat‐2

Abstract: Routine and accurate profiling of the sea surface height (SSH) in the Arctic is needed to continue these crucial time series and provide more detailed insights into these changes. While we can reliably monitor the SSH of the open oceans at lowto-mid latitudes using satellite altimetry data (IPCC, 2019), continuous and widespread measurements at high-latitude ice-covered seas have remained limited. The main challenges are the reduced coverage due to the low inclination orbit of most satellite altimeters, sea su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The weak beams are ∼1/4th of the strong beams, and thus we expect lower precision and longer segment‐lengths of ATL10 when using weak beams (Bagnardi et al., 2021 also noted that preliminary studies of the IS2 Project Science Office have identified range biases across the beams of centimetre‐levels), as the study by Bagnardi et al. (2021) identified an overall a small inter‐beam bias on sea surface height anomalies over the Arctic Ocean between the strong beams of beam‐pair 1 (GT1R) and beam‐pair 3 or 5 (GT3R/GT5R) of ∼3 cm. One could consider using only the strong beams (and potentially only one beam) to limit potential impact on precision, however as we have shown (Figure S1 in Supporting Information ), limited data was available when generating C2I tracks when considering small search radii (by excluding beam‐pairs far away), and when using only strong beams (not shown).…”
Section: Results Discussion and Conclusionmentioning
confidence: 93%
See 3 more Smart Citations
“…The weak beams are ∼1/4th of the strong beams, and thus we expect lower precision and longer segment‐lengths of ATL10 when using weak beams (Bagnardi et al., 2021 also noted that preliminary studies of the IS2 Project Science Office have identified range biases across the beams of centimetre‐levels), as the study by Bagnardi et al. (2021) identified an overall a small inter‐beam bias on sea surface height anomalies over the Arctic Ocean between the strong beams of beam‐pair 1 (GT1R) and beam‐pair 3 or 5 (GT3R/GT5R) of ∼3 cm. One could consider using only the strong beams (and potentially only one beam) to limit potential impact on precision, however as we have shown (Figure S1 in Supporting Information ), limited data was available when generating C2I tracks when considering small search radii (by excluding beam‐pairs far away), and when using only strong beams (not shown).…”
Section: Results Discussion and Conclusionmentioning
confidence: 93%
“…When considering systematic biases of IS2, its worthy to consider the impact on precision there is from including all six beams in the binning of IS2 observations. While studies have investigated the overall precision of IS2's weak and strong beams in the Arctic (Ricker et al., 2023) along with inter‐beam discrepancies (Bagnardi et al., 2021), it is not clear exactly what the impact is on derived freeboards over sea ice. The weak beams are ∼1/4th of the strong beams, and thus we expect lower precision and longer segment‐lengths of ATL10 when using weak beams (Bagnardi et al., 2021 also noted that preliminary studies of the IS2 Project Science Office have identified range biases across the beams of centimetre‐levels), as the study by Bagnardi et al.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially useful when observing the ocean's surface topography due to its high variability. By 1 August 2021, one year of passes had been collected, so that there were enough data to compare the two altimeter systems [13].…”
Section: Introductionmentioning
confidence: 99%